A standardized extract of Ginkgo biloba prevents locomotion impairment induced by cassava juice in Wistar rats - Rivadeneyra-Domínguez, Eduardo; Vázquez-Luna, Alma; Rodríguez-Landa, Juan F.; Díaz-Sobac, Rafael (Frontiers in Pharmacology, 2014)
The long-term consumption of cassava (Manihot esculenta Crantz) juice produce neurotoxic effects in the rat, characterized by an increased in motor activity in the open field test and presence of uncoordinated swim (i.e. lateral swimming), in the swim test; which has been associated with damage in the hippocampus (CA1). On the other hand, flavonoids content in the Ginkgo biloba extract has been reported to produces neuroprotective effects at experimental level; therefore we hypothesized that Ginkgo biloba extract may prevents the motor alterations produced by cassava juice and reduce cellular damage in hippocampal neurons of the rat. In present study the effect of vehicle, cassava juice (linamarin, 0.30 mg/kg), Ginkgo biloba extract (dry extract, 160mg/kg), and combination of treatment were evaluated in the open field and swim tests to identify locomotor and hippocampal alterations in adult male Wistar rats. All treatments were administered once per day, every 24 hours, for 28 days, by oral rout once. The effect was evaluated at 0, 7, 14, 21 and 28 days of treatment. The results show that cassava group from day 14 of treatment increase crossing and rearing in the open field test, as compared with the vehicle group; while in the swim test produces an uncoordinated swim characterized by the lateral swim. In this same group an increase in the number of damage neurons in the hippocampus (CA1) was identified. Interestingly, both behavioral and neuronal alterations produced by cassava juice administration were prevented by treatment with Ginkgo biloba extract. The results shown that Ginkgo biloba extract exert a protective effect against behavioral and neuronal damage associated with consumption of cassava juice in the rat. These effects are possibly related with flavonoid content in the Ginkgo biloba extract.